2013
DOI: 10.1177/0093854813500956
|View full text |Cite
|
Sign up to set email alerts
|

International Perceptions of Stalking and Responsibility

Abstract: This study investigates the influence of prior relationship and severity of behavior on perceptions of stalking and responsibility with a combined sample of 1,080 members of the community from Australia, the United States, and the United kingdom. Participants were presented with 1 of 12 versions of a hypothetical stalking scenario and responded to scale items regarding the behavior of a male perpetrator toward a female target. Prior relationship and severity of behavior influenced perceptions of stalking and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
2
17
0
1
Order By: Relevance
“…Ambiguous scenarios are more likely to be considered stalking when the behaviour is more persistent (either repeated for longer or more frequent), explicitly threatening, and there is clear intent to harm on the part of the perpetrator (Dennison, 2007;Dennison & Thomson, 2002;Phillips et al, 2004;Scott et al, 2014). Sheridan and Scott's (2010) findings suggest that people rely mostly on evidence of overt aggression when identifying stalking, to the exclusion of other indicators.…”
Section: Perceptions Of Stalkingmentioning
confidence: 95%
See 3 more Smart Citations
“…Ambiguous scenarios are more likely to be considered stalking when the behaviour is more persistent (either repeated for longer or more frequent), explicitly threatening, and there is clear intent to harm on the part of the perpetrator (Dennison, 2007;Dennison & Thomson, 2002;Phillips et al, 2004;Scott et al, 2014). Sheridan and Scott's (2010) findings suggest that people rely mostly on evidence of overt aggression when identifying stalking, to the exclusion of other indicators.…”
Section: Perceptions Of Stalkingmentioning
confidence: 95%
“…When presented with short stalking vignettes in which the prior relationship between victim and stalker is manipulated, all respondents, whether male or female, general community or police officers, are more likely to identify unwanted intrusions by strangers as stalking. Strangers are also judged to present a greater threat and require more police response than ex-partners or acquaintances (Hills & Taplin, 1998;Phillips, Quirk, Rosenfeld, & O'Connor, 2004;Scott, Lloyd, & Gavin, 2010;Scott, Nixon, & Sheridan, 2013;Scott et al, 2014;Sheridan, Gillett, Davies, Blaauw, & Patel, 2003;Weller, Hope, & Sheridan, 2013). Recent research by Scott and colleagues (2013) and Weller and colleagues (2013) demonstrates that even among police who have specialist training or direct experience with stalking cases, stranger stalkers are viewed as more problematic or a greater threat.…”
Section: Perceptions Of Stalkingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Hills and Taplin (1998) examined perceptions from the perspective of the 'victim' with an Australian student sample and found that behaviour is more likely to be perceived as fear invoking and as requiring intervention when perpetrated by a stranger rather than an ex-partner. Similarly, research examining perceptions from the perspective of an 'observer' with Australian, U.K. and U.S. student and community samples has found that behaviour is more likely to be perceived as stalking and as requiring intervention when perpetrated by a stranger rather than an ex-partner (e.g., Cass, 2011;Phillips, Quirk, Rosenfeld, & O'Connor, 2004;Scott, Rajakaruna et al, 2014;Sheridan, Gillett, Davies, Blaauw, & Patel, 2003). Behaviour is also more likely to be perceived as causing the target alarm or personal distress and fear of violence, as being reported to the police, and as requiring a restraining/intervention order or conviction when perpetrated by a stranger (e.g., Cass & Mallicoat, 2015;Scott, Rajakaruna et al, 2014;Scott, Lloyd, & Gavin, 2010).…”
Section: Prior Relationshipmentioning
confidence: 99%